Modem hypermedia systems, which encompass the ability to adapt to the properties of human memory and cognition - Woźniak, Piotr; Gorzelańczyk, Edward J. (Glottodidactica, 1999)
In this article we would like to show the need for developing knowledge access systems that can account for the imperfections in human perception, information processing and memory (Higgins et al., 1996). The implementation of such systems will result in enormous savings in the process of learning at all three stages of knowledge acquisition (by the mind): (1) access knowledge to, (2) learning and (3) knowledge retention (Clark et al., 1997). In particular, we will try to stress the importance of repetition spacing algorithms (Woźniak and Gorzelańczyk, 1994), as well as the importance of (1) (2) and the application of the newly introduced concept of processing, ordinal attributes in hypertext documents, semantics (Wiesman et al., 1997; Gillham, 1988).